2016
DOI: 10.1248/bpb.b15-00479
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Activities of Crebanine by Inhibition of NF-κB and AP-1 Activation through Suppressing MAPKs and Akt Signaling in LPS-Induced RAW264.7 Macrophages

Abstract: Crebanine, an aporphine alkaloid, displays various biological activities such as anticancer and antimicrobial activities. In this study, we further investigated the suppressive effect of crebanine on lipopolysaccharide (LPS)-induced expression of proinflammatory mediators and the molecular mechanisms underlying these activities in RAW264.7 macrophages. Crebanine inhibited the production of proinflammatory cytokines including interleukin-6 (IL-6) and tumor necrosis factor-alpha in LPS-induced RAW264.7 cells. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…Moreover, MAPKs have been involved in pro-inflammatory signaling cascades and large numbers of evidence has demonstrated that the activation of ERK1/2 and JNK is involved in up-regulation of nitric oxide and pro-inflammatory cytokines in LPS- induced macrophages [37, 38]. Thus, we assessed that 4'- O -Demethylophiopogonanone E inhibited the inflammatory response via blocking the phosphorylation of MAPKs in LPS-stimulated macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, MAPKs have been involved in pro-inflammatory signaling cascades and large numbers of evidence has demonstrated that the activation of ERK1/2 and JNK is involved in up-regulation of nitric oxide and pro-inflammatory cytokines in LPS- induced macrophages [37, 38]. Thus, we assessed that 4'- O -Demethylophiopogonanone E inhibited the inflammatory response via blocking the phosphorylation of MAPKs in LPS-stimulated macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MAPK signaling cascades are activated by LPS through binding of LPS to the TLR4 receptor, which is a critical factor in the signal transduction pathways involved in controlling inflammatory mediators in macrophages [42]. Several lines of evidence have shown that the activation of ERK1/2, p38, and JNK is involved in the regulation of AP-1 activity by increasing transcription [43,44]. To investigate the molecular mechanisms involved in the inhibition of inflammatory gene expression and their transcriptional activation, we examined the effects of CTB on LPS-induced MAPK phosphorylation in RAW264.7 cells using Western blot assays.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have demonstrated that inhibition of NF-B activation helps to drive the tumor-promoting phenotype of TAMs to antitumor phenotype [13, 39]. Redirecting M2-like TAM toward M1-like phenotype by reactivating NF-κB induced significant antitumor immune response in mammary carcinoma [40].…”
Section: Discussionmentioning
confidence: 99%